A Comparative Study of Protective Schemes for Shield Tunneling Adjacent to Pile Groups. (21st January 2020) - Li, Penglin; Lu, Yuquan; Lai, Jinxing; Liu, Houquan; Wang, Ke
Abstract : Shield tunneling adjacent to pile groups is always an unavoidable problem in urban metro construction. A case was found in the project of Tianjin Metro Line 7, where a shield tunnel would be constructed near the existing pile groups of Shiyou Bridge. The whole shield tunnel is close to pile groups, and the minimum distance is only 0.8 m. Therefore, four kinds of protective schemes are proposed in this paper. It is vital to select an appropriate protective scheme to guarantee the safety during the tunnel construction. In this study, the main mechanical characteristic and physical parameters of site soil were obtained through laboratory tests. Besides, the three-dimensional finite element method was carried out to compare and analyze the effectiveness of the protective schemes in mitigating the effects of tunneling on adjacent pile groups. The results show that the deep-hole grouting scheme has better control effect on the lateral deformation and bending moment of piles, while the pile foundation underpinning scheme has better effectiveness on reducing the settlement of bridge structure and ground deformation. Finally, the deep-hole grouting reinforcement scheme will be adopted to ensure the shield passing through the pile groups smoothly.